Development and characterization of stainless steel fiber-based copper-free brake liner formulation: A positive solution for steel fiber replacement - R. Vijay; D. Lenin Singaravelu; R. Jayaganthan (Friction)
Abstract This study deals with the development of drum brake liner for a multi-utility vehicle possessing a hydraulic brake system by varying 7 weight % of steel fiber and stainless steel fiber each, in friction composite formulations. The developed friction composites were tested for physical, chemical, corrosion, mechanical, thermal properties, and tribological characteristics, under near-actual conditions using an inertia dynamometer as per industrial standards. Finite element analysis software (ANSYS) analysis was performed to show the thermal stress distribution of the developed friction composites at the maximum temperature rise due to heat generated during brake stops, and an extensive evaluation method was used to rank the composites. The study concludes that the brake factor of the stainless steel fiber-based friction composite produces stable performance in all conditions with a lower liner temperature rise of 340 °C and lower thermal stress at 4.255294 MPa. However, the steel fiber-based composites produced high performance at the beginning but deteriorated after a certain period due to higher levels of corrosion and a high temperature rise of 361 °C resulting in a negative fade (−0.84%) and more thermal stress (5.619102 MPa). The primary plateau, secondary plateau, back transfer of drum wear debris, and the distribution of constituents on the worn surface of the developed composites in a resin matrix were identified and studied using a scanning electron microscope (SEM) equipped with energy-dispersive spectroscopy.